Evaluation of the use of Wastewater Based Epidemiology as a Surveillance Tool and the Potential effects of Vaccines and Students Beliefs and Practices in Mitigating the Spread of COVID-19 Among Students at East Carolina University - White, Avian (East Carolina University, 2022)
Worldwide, newly emerging and re-emerging infectious diseases and pathogens have led to increases in the number and frequency of disease outbreaks. Although these disease outbreaks are not new, increases in outbreaks have led to the need for public health agencies to effectively monitor disease spread. It has been estimated that 25% of 60 million deaths occurring yearly are the result of infectious diseases (Fauci et al., 2005; Nii-Trebi, 2017). Thus, disease monitoring tools are of utmost importance. The outbreak and spread of a severe acute respiratory illness in China alerted the world to a potentially new or re-emerging pathogen. As the virus rapidly spread, it was named "Severe Acute Respiratory Syndrome 2" (SARS-CoV-2) by the World Health Organization (WHO). The SARS-CoV-2 virus was deemed a public health emergency and later declared a pandemic as people across the world contracted COVID-19. The rapid spread of the COVID-19 pandemic underscored the need for disease monitoring and surveillance to mitigate spread. SARS-CoV-2 causes fever, dry cough, shortness of breath and in some instances loss of taste and smell. However, some persons, particularly those with pre-existing conditions, may experience severe symptoms of high fever, severe cough pneumonia, and even death (WHO, 2020). In the United States alone, an estimated 88,044,073 cases have occurred since the start of the epidemic (Worldometer, 2022). Early strategies to handle the epidemic included temporary sheltering in-place orders, and many institutions including schools and universities shifted to online strategies to ensure continuity in learning. As these entities later sought to fully re-open and regain a sense of normalcy, many were tasked with establishing monitoring systems to help detect potential outbreaks. The use of wastewater-based surveillance was evaluated as a tool in helping to identify when and where student polymerase chain reaction (PCR) testing should be conducted. Here, we utilized wastewater-based epidemiology by sampling dormitory wastewater thrice weekly during Spring and Fall 2021. Data obtained from this sampling was used to help identify potential cases of COVID-19 in dormitories. Additionally, as vaccines were developed and distributed, the relationship between vaccination rates and COVID-19 cases on campus was investigated. Lastly, students' attitudes and behaviors toward the virus were also evaluated by administering an online survey tool designed through REDCAP systems. This survey utilized a Likert scale where possible to aid in analysis and comparison of student responses between Spring 2021 and Fall 2021 semesters. Results from this study found significantly higher concentrations of SARS-CoV-2 in wastewater were observed during the Spring relative to the Fall semester. Dorms with higher numbers of COVID-19 cases also had higher concentrations of SARS-CoV-2 in their wastewater. A significant inverse relationship was observed between vaccine rates and student COVID-19 cases. As vaccinations rates increased within the dormitories, the number of student cases decreased. Students became more receptive to the vaccine in the Fall semester in comparison to the Spring. This change in attitudes may have helped the University's vaccination rates in the Fall semester thus affecting student COVID-19 rates. Here, we saw students a significant difference in virus perception between Spring 2021 and Fall 2021 semesters. Specifically, a lower number of students having a negative perception of the virus. Additionally, students reported having less restrictive behavior (e.g., visitors, mask wearing) in Fall 2021 compared to Spring 2021. Overall, this study showed that universities may successfully use surveillance techniques such as wastewater-based epidemiology to help determine when swarm testing of students should be initiated. It also provided evidence that vaccination campaigns may have helped to reduce the incidence rate of COVID-19 on campus. Gaining an understanding of how students feel and behave regarding the threat of disease outbreaks, the implementation of various preventative measures, and the effects that changes in educational delivery platforms may have on learning and social interactions are also important for developing successful programs to mitigate the spread of diseases.
Keywords: Wastewater Epidemiology; COVID-19; Wastewater-Based Epidemiological Monitoring; Universities; Students; Vaccines